Stability of Back Propagation Training Algorithm for Neural Networks (Baghdad Science Journal, 2012)
In this paper, we derive and prove the stability bounds of the momentum coefficient µ and the learning rate ? of the back propagation updating rule in Artificial Neural Networks .The theoretical upper bound of learning rate ? is derived and its practical approximation is obtained